Utilization of Keyboard Drums at the Karo Ethnic Youth Year Work Party in Mardinding Village, Mardingding District, Karo Regency - Immanuel Sinaga; Emmi Simangunsong; Happy Majesty Waruwu (Institut Seni Indonesia Padangpanjang, 2025)
This study discusses the use of keyboard drums at the Karo ethnic youth work party in Mardingding Village, Mardinding District, Karo Regency. This study uses descriptive qualitative research. The results of the study indicate that the use of keyboard drums is currently used in almost every Karo ethnic activity or traditional ceremony, because the keyboard is a digital musical instrument with a music program (style) that can produce sounds like the Karo ethnic traditional instrument, the five sendalanen drum. The functions contained in this year's work party are the function of music as an aesthetic appreciation, the function of music as entertainment, the function of music as an emotional expression, the function of music as a means of communication, the function of music as a physical reaction, the function of music as related to social norms, the function of music as a sustainable contribution, the function of music as social integration. This event was held to unite residents in Mardingding District, Tanjung Pamah Village, Bandar Purba Village, and Lau Solu Village